PENGARUH HARGA, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA FCK DIGITAL PRINTING SOLUTION MALANG - Niajeng Putri Ulfa Hakim; Anis Dwiastanti; Roni Angger Aditama (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2023)
The purpose of this study seeks to analyze Price, Product Quality, and Service Quality both partially and simultaneously on Consumer Satisfaction and analyze the dominant influence between Price, Product Quality, and Service Quality on Consumer Satisfaction. The population in this study is all consumers of FCK Digital Printing Solution Malang. While the sample was taken using a problability sampling technique with random sampling and obtained a sample of 96 respondents. The examination utilized in this study was various direct relapse investigation. That's what the outcomes showed (1) to some extent the Cost variable affected Shopper Fulfillment, (2) to some degree the Item Quality variable doesn't influence Customer Fulfillment, (3) somewhat the variable Help Quality affects Buyer Fulfillment, (4) at the same time there is a huge impact between Value, Item Quality, and Administration Quality on Purchaser Fulfillment. The extent of impact was 53.1%, while the excess 46.9% was affected by different factors that were excluded from this review, (5) the Assistance Quality variable had the best effect on Consumer loyalty.  Keywords: Price, Product Quality, Service Quality, and Customer Satisfaction